THE EFFECT OF WORK MOTIVATION, WORK DISCIPLINE AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE IN INDOMARET SHOP IN SOUTH SURABAYA - Alan Margia Hermawan; Bayu Airlangga Putra; Mochammad Arif (Journal of World Conference (JWC), 2019)
This study aims to determine the relationship between work motivation, work discipline andculture organizationalon improving employee performance at the Indomaret store in South Surabaya. This research is a quantitative researcher. With a population of 62 respondents. Data collection techniques using interviews, observation and questionnaires. The data analysis used is validity test, reliability test,assumption classictest and multiple linear analysis test. The results of the study influence the work motivation, work discipline andculture organizationalon the performance of indomaret shop employees in south Surabaya. Shows that there is arelationship positive and significantof F test 253.257> 3.15 simultaneously. Partially work motivation -0,501 <t1,670 has no significant effect on employee performance, work discipline 0,795 <t table 1,670 has no significant effect on employee performance and organizational culture 19,861> t table 1,670 has a significant influence on employee performance.